Adult Education Students' Perceptions towards Teaching and Learning Mathematics: A qualitative Study - Bakmani , Mohammed; Khalil, Ibrahim (Dirasat: Educational Sciences, 2023)
Objectives: The study aims to investigate how adult education students in Saudi Arabia perceive mathematics education and learning. Methods: The study adopted a qualitative approach and utilized various data collection tools, including interviews, observations, and open questionnaires. Intentionally, the sample was selected; a total of 18 students from the preparatory stage of adult education, specifically affiliated with the Haridha Education Office in Rijal Alma' Governorate, participated in the study. Results: The study yielded several key findings. Firstly, the students perceive the significance of mathematics in addressing for solving daily problems, its connection to other sciences, and its benefits being limited to the four basic operations from their perspective. Additionally, they unanimously recognized the importance of mathematics as an academic discipline, and its role in developing thinking, creativity, and mental faculties. The results further indicated multiple challenges in teaching and learning mathematics, such as the diversity of ideas presented in the lesson, the length of study breaks, and some students' difficulty in grasping mathematical knowledge. Conclusions: The study recommended that there is unanimous consensus among adult education students on the importance of mathematics as a science as well as a subject of study, highlighting its importance in addressing daily problems and promoting critical thinking. Additionally, there is recognition of the teacher's crucial role in fostering educational experiences and shaping their attitudes towards mathematics.